UPAYA PEMERINTAH DESA DALAM PEMBERDAYAAN PEREMPUAN PADA KELOMPOK WANITA TANI MATAHARI - Amanda, Vannia Tri; Amaliatulwalidain, Amaliatulwalidain; Isabella, Isabella (Jurnal Progress Administrasi Publik, 2023)
The village government's efforts in empowering women through the Matahari Farmer Women's Group program in Rantau Kasih Village, Lawang Wetan District, Musi Banyuasin Regency to provide positive and productive activities to mothers and, encourage and help the family economy. However, in this case, there is still a lack of understanding, knowledge, and attention given by the rantau kasih village government is also still lacking so that this program has not received optimal support to face the problems faced.  The purpose of this study is to determine the process and benefits of village government efforts in empowering women in the sun farmer women's group in rantau kasih village. The research method used by the author is qualitative research method. Data collection techniques in this study used observation, interviews and documentation. Data analysis techniques consist of data collection, data reduction, data presentation, and conclusions. The results of this study show that the village government's efforts in empowering women in the sun farmer women's group (KWT) program in 2022 in Rantau Kasih village are declared quite successful. The stages include planning, implementation, monitoring, and evaluation, and each has an important role in achieving the goals of KWT Matahari.   Keywords: Group Matahari Farmer Women's Group; Village Government Efforts; Empowerment.